Diabetes and Aging-related Complications (Springer Singapore, 2018)
This book addresses why and how the aging process is accelerated under diabetes, providing valuable and comprehensive information for the management of various types of diabetes- and aging-related disorders. Since several papers have shown that average life span and healthy life expectancy are reduced in diabetic patients, especially in those with a long history of disease, the early detection and treatment of diabetes-related complications are urgently needed in order to slow the aging process and help people successfully live with diabetes. Each chapter of this book addresses a specific diabetes and aging-related complication. The topics covered include not only diabetic vascular complications, the leading causes of morbidities and high mortality rates in both type 1 and type 2 diabetic patients, but also other aging-related complications such as Alzheimer's disease, osteoporosis, periodontitis and cancer growth and metastasis. Experts on each topic discuss the background of the aging process and methods for coping with diabetes-related complications. The book as a whole, as well as the individual chapters, offer a valuable resource for researchers and practitioners in the fields of diabetic studies, gerontology, and aging science.